Developing Clostridia as Cell Factories for Short- and Medium-Chain Ester Production - Wang, Qingzhuo; Al Makishah, Naief H.; Li, Qi; Li, Yanan; Liu, Wenzheng; Sun, Xiaoman; Wen, Zhiqiang; Yang, Sheng (Frontiers in Bioengineering and Biotechnology, 2021)
Short and medium-chain volatile esters with flavors and fruity fragrances, such as ethyl acetate, butyl acetate and butyl butyrate, are usually value-added in brewing, food, and pharmacy. The esters can be naturally produced by some microorganisms. As ester-forming reactions are increasingly deeply understood, it is possible to produce esters in non-natural but more potential hosts. Clostridia are a group of important industrial microorganisms since they can produce a variety of volatile organic acids and alcohols with high titers, especially butanol and butyric acid through the CoA-dependent carbon chain elongation pathway. This implies sufficient supplies of acyl-CoA, organic acids, and alcohols in cells, which are precursors for esters production. Besides, some Clostridia could utilize lignocellulosic biomass, industrial off gas, or crude glycerol to produce other branched or straight chain alcohols and acids. Therefore, Clostridia offer great potential to be engineered to produce short and medium-chain volatile esters. In the review, the efforts to produce esters from Clostridia via in-vitro lipase-mediated catalysis and in-vivo alcohol acyltransferase (AAT)-mediated reaction are comprehensively revisited. Besides, the advantageous characteristics of several Clostridia and clostridial consortia for bio-esters production, and driving force of synthetic biology to clostridial chassis development are also discussed. It is believed that synthetic biotechnology should enable the future development of more effective Clostridia for esters production